NANOPARTÍCULAS MULTIFUNCIONAIS DE ÓXIDO DE TITÂNIO E ÓXIDO DE MOLIBDÊNIO COM PRATA: SÍNTESE, CARACTERIZAÇÃO E PROPRIEDADES ANTIMICROBIANAS - Pompeu, Lenise Deon (2018)
Infections in the nails can be caused by different fungi, among them, the main causes are the dermatophytes, which are the causative agents of mycosis of this type. In order to have an alternative for the treatment of these infections, a titanium oxide and molybdenum oxide compound with silver nanoparticles (Ag) was carried out, in order to evaluate and cooperative effect of the two systems on antibacterial and antifungal activity. The oxides were prepared by hydrothermal synthesis and characterized by X-ray diffraction, scanning electron microscopy, infrared, zeta potential at different pH, ultraviolet-visible spectroscopy, determination of antimicrobial activity and photocatalytic activity. The presence of Ag was confirmed by energy dispersion X-ray spectrometry. In the scanning electron microscopy, the presence of silver nanoparticles was shown to be compatible with the sizes of crystallites obtained by X-ray diffraction. At the zeta potential, the oxide particles have a more positive displacement with the inclusion of silver. For the infrared analysis it was possible to observe the vibrations of the chemical bonds. In general it can be observed that the nanoparticles were efficient for the inhibition and / or inactivation of the mycoorganisms.